Barriers and facilitators to physical activity and further digital exercise intervention among inactive British adolescents in secondary schools: a qualitative study with physical education teachers - Moore, Richard; Edmondson, Lee; Gregory, Maxine; Griffiths, Kerry; Freeman, Elizabeth (Frontiers in Public Health, 2023)
Background Previous studies indicated that physical education programs in schools were unsuccessful to ameliorate physical activity (PA) behaviors among adolescents. This study investigated PE teachers’ perceptions of barriers and facilitators to PA and further digital exercise interventions among inactive British adolescents in secondary schools based on the Capability, Opportunity, Motivation, and Behavior (COM-B) model, the Behavior Change Wheel (BCW), and Theoretical Domains Framework (TDF). Method A qualitative study was conducted among 156 PE teachers in England. deductive thematic analysis approach was applied to analyze data. Results A comprehensive perception of PE teachers revealed 21 barriers to PA among inactive adolescents in secondary schools. The study findings show that barriers exist across all categories of the COM-B model in physical opportunity (7), reflective motivation (5), social opportunity (4), psychological capability (4) and physical capability (1). The majority of these barriers were reported in previous studies as being barriers to PA from the perspective of children and adolescents. This shows that the findings are consistent with the views of children and adolescents that participated in these studies. Particular salient barriers for inactive adolescents were reported and greater insight into their experiences was highlighted. The study reported the main sources of behavior, intervention functions, policy functions, and behavior change tools that can be used for future behavior change interventions to support inactive adolescents. Conclusion The study recommends using its findings to design interventions for inactive adolescents to achieve recommended levels of physical activity (PA). The study’s comprehensive approach and evidence-based solutions provide extensive reference points for future intervention design, informing policy and contributing to enhancing support for inactive adolescents. Further development of digital exercise interventions, including conversational artificial intelligence (AI), is suggested to engage adolescents at scale and provide personalized support to overcome multiple barriers to PA.